The in silico search for endogenous anti‐Alzheimer's compounds: Nonhuman/Novel screening strategies. (7th December 2020) - Weaver, Donald F; Barden, Christopher; Gupta, Mayuri; Meek, Autumn; Reed, Mark; Wang, Yanfei; Wu, Fan
Abstract: Background: Since many peptide and proteins are susceptible to oligomerization analogous to Aβ and tau, there is evolutionary pressure to inhibit deleterious protein misfolding; likewise, the immunoinflammatory cascade triggered by such misfolding is also subject to homeostatic regulation. Accordingly, it is reasonable to postulate the existence of endogenous molecules within the human brain that could modulate or even interrupt the neurotoxic cascade of AD by blocking both the proteopathy and immunopathy of Alzheimer's disease (AD). Such compounds would constitute platforms for future drug development. Method: We sought to identify a single anti‐proteopathic and anti‐immunopathic agent endogenous to the human central nervous system; to find this compound, we created a comprehensive library of 1, 376 molecules (molecular weight < 600 Da) naturally occurring within the human brain and employed an in silico screening assay. Using computer‐aided screening with a molecular mechanics force field, we docked these endogenous molecules against computer models of in Aβ(HHQK16 LVFF), tau(KKAK144 ), IL‐1R1(HKEK80), IL‐1β(KLRK76), C1qA(KKGH225), IFN‐gamma(KKKR112) and RANTES(RKNR70 ). Additional molecular dynamics simulations were done to refine the docking. Finally, multiple in vitro assays were done, verifying that the in silico hits had correctly predicted the ability to block oligomerization and to bind to multiple immunopeptides. Result: Several zwitterionic and aromatic‐anionic compounds capable of binding to these multiple amyloid, tau and immunoprotein targets were identified. Strong in silico hits included 2‐aminoethanesulfonic acid, L‐phosphoserine, 5‐hydroxytryptamine and 3‐hydroxyanthranilic acid. These predictions were verified using in vitro assays, including the kinetic Thioflavin T [ThT] aggregation assay. Conclusion: Searching for an "endogenous anti‐AD compound" represents an unexplored concept. Our in silico and in vitro studies suggest that compounds endogenous to the human brain can inhibit pathological both the proteopathic and immunopathic pathogeneses of AD. The value of a novel in silico screening assay to identify such endogenous agent capable of "one‐drug‐multiple‐targets" has also been demonstrated.